(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
This paper presents the results of the experimental investigation on the shear performance of beams strengthened with different types of grids (i) GFRP (Glass Fiber Reinforced Polymers) mesh; (ii) geogrid; and (iii) steel mesh. The experimental program reports the test results of twelve reinforced-concrete (RC) beams strengthened internally with dimensions of 1200 mm in length, 150 mm in width, and 200 mm in depth that were constructed and tested up to failure using a four-point load configuration. One beam is considered as a control beam, and the other beams are divided into three groups; each group is strengthened with different material mesh. Various parameters were considered in this study, including the number of mesh layers, the type of reinforcement material mesh, and the strengthening configurations. The test results indicated that beams strengthened with steel meshes achieved a peak shear load of 174 kN with an increase of 66% compared with the control beam. While the development in the ultimate load for strengthened beams using GFRP ranged from 1% to 18% compared to the control beam. Insufficient improvement in the ultimate load for beams strengthened using geogrid is obtained from the experimental results.